PENGARUH CURCUMIN TERHADAP KADAR KOLESTEROL TOTAL, LDL-KOLESTEROL, JUMLAH F2 -ISOPROSTAN, DAN SEL BUSA (FOAM CELL) DINDING AORTA PADA TIKUS DENGAN DIET ATEROGENIK - Fikriah, Ika; Kalim, Handono; Dradjat, Respati Suryanto (Fakultas Kedokteran Universitas Brawijaya, 2005)
ABSTRACT Death caused by cardiovascular and cerebrovascular diseases are still the highest. Atherosclerosis due to hypercholesterolemia is a predispositioning factor of both diseases. Curcumin has an antioxidant character that can inhibit lipid peroxidase to atherogenesis process. The aim of this study was to observe the effect of curcumin in decreasing total cholesterol level, LDL-cholesterol, the number of F2-isoprostan and foam cell of aorta’s wall of white rats strain wistar after giving atherogenic diet for 10 weeks. There were 6 groups in this study (n=24): atherogenic diet group (group I as positive control), atherogenic diet group + curcumin 50 mg/kg b.w. per day (group II), atherogenic diet group + curcumin 100 mg/kg b.w. per day (group III), atherogenic diet group + curcumin 200 mg/kg b.w. per day (group IV), atherogenic diet group + curcumin 400 mg/kg b.w. per day (group V), normal diet group (group VI as negative control). After 10th, the level of total cholesterol and LDL-cholesterol were measured by spectrofotometri. Staining F2-isoprostan was done with Avidin Biotin Complex imunohystochemistry method, and staining foam cell with HE-oil Red O. The number of F2-isoprostan and foam cells were counting semi quantitatively using light microscope. The highest total cholesterol level was found in group I (275,15 ± 10,01; Mean ± SD), the highest LDL-cholesterol level was found in group I (158,15 ± 12,19). Statistically total cholesterol level and LDL-cholesterol level in group I were significantly higher (p ≤ 0,05) than other